Enhancing the speech technology educational software and modules for motorola charity project for primary and secondary school - Sheikh Hussain Shaikh Salleh; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Bioperubatan dan Sains Kesihatan (Skudai, Johor : Penerbit UTM, 2008)
Includes bibliographical references